Methanol Production via CO2 Hydrogenation on Promoted Cu-based Catalyst - Omar Baslasl, Maher Saleh (Universiti Teknologi PETRONAS, 2016)
This work will focus on the development of the methanol synthesis catalyst to find promising catalyst to increase the methanol selectivity and long life activity. A number of studies on this reaction have been reported over copper Cu-based catalysts on Alumina Support (Cu/ZnO/Al2O3). This catalyst undergoes to deactivation process due to the water produced from the reaction and also due to the heat released from the reaction. This paper will mainly focus on synthesizing the copper based catalyst on the Carbon Nanotubes (CNTs) as catalyst support for CO2 hydrogenation to synthesize methanol. The author is focusing on the effect of adding promoters such as niobium (Nb) and zirconium (Zr) on the properties of catalyst.